Knowledge Analysis of Women of Childbearing Age (15-49 Years) about Personality Hygiene with the Incident of Vaginal Discharge in the Krian Sidoarjo Health Center Area - Riza Tsalatsatul Mufida; Erma Retnaningtyas; Miftakhur Rohmah; Siti Julaichah (STRADA : Jurnal Ilmiah Kesehatan, 2023)
The high rate of vaginal discharge in the Krian Sidoarjo Health Center area is due to the fact that many women of childbearing age do not know about vaginal discharge, so they perceive vaginal discharge as something that is normal and trivial, besides that the feeling of embarrassment when women experience vaginal discharge often makes these women reluctant to consult a doctor. This study aims to analyze the knowledge of youth aged 15-49 years about personal hygiene with the incidence of vaginal discharge in the Krian Sidoarjo Health Center area. Research using analytical methods with the approach cross sectional. The sample used a sampling technique with stratified random sampling method, namely 98 samples from a total population of women of childbearing age (15-49 years) of 4870 people. This study used a questionnaire as an instrument and data analysis used a test Who Square.